Wakaf Uang Sebagai Peluang Ekonomi Syariah Kontemporer - Ulum, Bahrul; Astari, Puji; Setiawati, Rini; Yanti, Fitri (Badan Wakaf Indonesia, 2024)
Abstrack: Cash waqf is a type of productive waqf that is currently in demand by the public with a system that makes it easier for people to donate waqf. Obstacles to developing cash waqf include the lack of public understanding about cash waqf and the challenges of developing the value of cash waqf. The aim of this research is to explain the scope of cash waqf, to find out contemporary and safe cash waqf development programs. This method uses qualitative research with library research analysis where information and data are collected with the help of various kinds of materials in the library such as reference books, results of similar previous research, articles, notes, and various journals related to the problem you want to solve. The results of this research are that cash waqf has the potential to have high beneficial value for the people. LKS-PWU as the cash waqf nazhir is responsible for managing and developing cash waqf. In terms of waqf management, management money must be based on Government Regulation Number 42 of 2006 Clause 48. Keywords: